Differential Diagnosis and Proper Treatment of Acute Rhinosinusitis: Guidance Based on Historical Data Analysis. Issue 2 (June 2017) - Cevc, Gregor
Background: The time course of rhinovirus positive and negative rhinosinusitis has not been quantified yet, which aggravates proper selection and justification of the optimum treatment for this illness. Such quantitative information would facilitate an early and proper identification of the disease and its differentiation from acute bacterial rhinosinusitis, and could diminish harmful overuse of antibiotics, arguably driven by patients' want for attention and the treating physicians' inability to offer an adequate verbal comfort in its stead. Objective: Extraction of the quantitative information needed to identify rhinovirus positive or negative rhinosinusitis and to allow selection of the most appropriate treatment from the published time dependence of individual clinical symptoms of the disease. Methods: Scrutiny (and modeling) of temporal evolution of all noteworthy symptoms of rhinosinusitis with a simple mathematical expression that relies on two adjustable parameters per symptom (and potentially a general time offset as an extra adjustable parameter). Results: Adverse effects of rhinosinusitis can be grouped according to the sequence of their exponential appearance and 2.6 times slower exponential disappearance, rhinovirus negative rhinosinusitis generally improving 25% faster and being 40% less severe. The major early local symptoms (throat soreness and scratchiness, headache) vanish with a half-life of 1.8 days, whereas further local symptoms take 1.6 times longer to disappear. At least 50–60% improvement of two prominent early symptoms, sore throat and sneezing (but not of nasal discharge, cough, and hoarseness) by day 5 of the disease implies a nonbacterial origin of rhinitis and should exclude use of antibiotics. Conclusion: Temporal evolution of all rhinosinusitis symptoms is qualitatively similar, which makes the early symptom decay a good proxy for, and predictor of, the disease perspective. Knowing a symptom intensity at just three to four time points suffices for reconstructing its entire time course and total intensity or gravity. This permits an easy and early identification of rhinosinusitis, and its plausible differentiation from acute bacterial rhinosinusitis, disease treatment optimization, and corresponding clinical trials simplification and/or shortening.